Signet-ring cells in the skin: a case of late-onset cutaneous metastasis of gastric carcinoma and a brief review of histological approach - Özgür Gündüz; Mehmet Can Emeksiz; Pınar Atasoy; Mehtap Kıdır; Selim Yalçın; Serkan Demirkan (PAGEPress Publications, 2017)
Up to 10% of patients with visceral malignancies develop skin metastases during their clinical course and these metastases constitute about 2% of all skin cancers. Skin metastasis may be the first sign of a clinically silent visceral cancer or represent recurrence of an internal malignancy. In both situations, they are associated with poor prognosis, which can partly be attributed to underdiagnosis. In this paper, a case of relapsing gastric adenocarcinoma, which manifested itself as asymptomatic cutaneous papules and nodules on a patient's head and neck, is reported and histopathological approach to the cutaneous lesions containing signet-ring cell is briefly reviewed.